Reduction in vehicle operating costs with the introduction of a public transit central terminal in the central business district of Manila - Genuino, Ernesto S.
This paper discusses the desirability of providing a Public Transit Central Terminal (PTCT) in the Central Business District (CBD) of Manila, together with the attendant considerations in the establishment pf such complex facility. An attempt is also made to estimate the reduction of vehicle operating costs which can be anticipated as a direct benefit from the provision of the PTCT due to the removal of loading and unloading activities from the streets of the CBD which activities will be transferred to the PTCT where they properly belong. This calculation is based on traffic, travel time and delay data, and vehicle characteristics taken from the Metro Manila Traffic Engineering and Management (TEAM) Project of the Ministry of Public Highways (MPH) while data on the cost of congestion are taken from the Transportation and Traffic Engineering Handbook of the Institute of Traffic Engineering Handbook of the Institute of Traffic Engineers edited by Beerwald, Huber and Keefer, which, in turn, are taken from a study by P.J Claffey, Running Costs of Motor Vehicles as Affected by Road Design and Traffic. These congestion cost data are modified to reflect the vehicle composition and costs of fuel, tires and parts as applicable in the CBD.